Utility analysis of an adapted Mini-CEX WebApp for clinical practice assessment in physiotherapy undergraduate students - Fuentes-Cimma, Javiera; Fuentes-López, Eduardo; Isbej Espósito, Lorena; De la Fuente, Carlos; Riquelme Pérez, Arnoldo; Clausdorff, Hans; Torres-Riveros, Gustavo; Villagrán-Gutiérrez, Ignacio (Frontiers in Education, 2023)
Clinical workplace-based learning is essential for undergraduate health professions, requiring adequate training and timely feedback. While the Mini-CEX is a well-known tool for workplace-based learning, its written paper assessment can be cumbersome in a clinical setting. We conducted a utility analysis to assess the effectiveness of an adapted Mini-CEX implemented as a mobile device WebApp for clinical practice assessment. We included 24 clinical teachers from 11 different clinical placements and 95 undergraduate physical therapy students. The adapted Mini-CEX was tailored to align with the learning outcomes of clinical practice requirements and made accessible through a WebApp for mobile devices. To ensure the validity of the content, we conducted a Delphi panel. Throughout the semester, the students were assessed four times while interacting with patients. We evaluated the utility of the adapted Mini-CEX based on validity, reliability, acceptability, cost, and educational impact. We performed factor analysis and assessed the psychometric properties of the adapted tool. Additionally, we conducted two focus groups and analyzed the themes from the discussions to explore acceptability and educational impact. The adapted Mini-CEX consisted of eight validated items. Our analysis revealed that the tool was unidimensional and exhibited acceptable reliability (0.78). The focus groups highlighted two main themes: improving learning assessment and the perceived impact on learning. Overall, the eight-item Mini-CEX WebApp proved to be a valid, acceptable, and reliable instrument for clinical practice assessment in workplace-based learning settings for undergraduate physiotherapy students. We anticipate that our adapted Mini-CEX WebApp can be easily implemented across various clinical courses and disciplines.